Pull-Through in Patients after Pelvic Anastomosis Leak Following Proctectomy: A Cross-Sectional Study - Davoodabadi, Hasan; Aldraji, Mohammad; Farahani, Abdolhosein Davoodabadi; Soltani, Parnian; Alemrajabi, Mehdi (Journal of Coloproctology, 2021)
Introduction Colorectal cancer is the second most common type of cancer and the third leading cause of mortality due to cancers. Anastomosis leak after proctectomy is a dangerous complication that must be managed carefully. The aim of the present study was to assess the procedure of resection and pull-through of the new rectum after anastomosis leak in patients after proctectomy.Methods and Materials This was a cross-sectional study. Patients who visited the Firoozgar Hospital between 2015 and 2018 for rectal cancer surgery and had anastomosis leak entered the study. All patients underwent resection of the residue of rectum and pull-through of colon.Results In the present study, out of the 110 cases who underwent proctectomy, 12 patients with postoperative anastomosis leak were reported. Five (41.7%) were male and 7 (58.3%) were female. The mean age of the patients was 41.5 ± 4.3 years (33–51). Resection of the new rectum and pull-through anastomosis were performed for these 12 patients. No major intraoperative complication occurred. Postoperative course was uneventful in all patients.Discussion Resection of residue of rectum and pull-through in patients with anastomosis leak can be done after rectal cancer surgery. This method is superior to abdominopelvic resection in many aspects, especially regarding accessibility to the new rectum by rectal exam or endosonography to assess recurrence or a relative continence after closure of ostomy.
Keywords: rectal cancer; anastomosis leak; proctectomy